The pre-acquisition process: the temporal hiatus between the announcement and completion in foreign acquisitions in Brazil - Ferreira, Manuel Portugal (2021)
Purpose – The purpose of this paper is to focus on the pre-acquisition process and, specifically, how the complexity involved in the transaction may drive the temporal gap between the formal announcement and the completion of the deal. The authors emphasize the time (in days) between announcement and completion. Design/methodology/approach – The empirical setting consists of the cross-border acquisitions (CBAs) of Brazilian firms by multinational corporations announced between 2008 and 2012. Using a sample of 741 acquisitions, the authors examine how institutional (cultural and regulatory) and technological complexity and the predictable mitigating effect of prior acquisition experience in Brazil all impact on the time needed for evaluating the target and negotiating. Findings – The results show that these complexity factors do matter for hastening the process and that recent experience with acquisitions in Brazil shortens the time needed to completion. Originality/value – This study contributes to the literature on the acquisition process and the uncertainty and complexity factors in CBA in an emerging economy.